The Implementasi E-ABK dalam Upaya Kebijakan Pemenuhan Pegawai pada Bagian Hukum dan Kerja Sama Kota Surabaya - Lesanti, Putri; Muljanto, Muhammad Agus (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to describe and describe the implementation of E-Workload Analysis in the process of fulfilling employees in the Legal and Cooperation Section of the City of Surabaya which is adjusted to the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 1 of 2020 concerning position analysis and workload analysis and in Mayor Regulation Number 104 of 2023 concerning the work system within the Surabaya City Government for bureaucratic simplification. This study uses Edward III's theory of the policy implementation model using four influencing indicators, namely, communication, resources, disposition and bureaucratic structure. This research is a qualitative descriptive research with observation techniques adapted to data from the Legal and Cooperation Section of the City of Surabaya. The results of the study show that the implementation of the e-Workload Analysis policy in fulfilling employees in the Legal and Cooperation Section of the City of Surabaya has met the requirements and is in accordance with the workload borne by employees in each position because it is adjusted to its supporting aspects. However, in the implementation of filling out the e-ABK itself, there are still delays in filling because there is work that must be done, apart from that, there are still employees who do not understand the technical aspects of the work so that it is necessary to re-assist.